A New Parameter-Extraction Method for DGS and its Application to the Low-Pass Filter - Haiwen Liu; Xiaowei Sun; Zhengfan Li (Active and Passive Electronic Components)
A new and simple parameter-extraction method for the equivalent circuit of defected ground structure (DGS) is presented. Using this method, circuit simulation, based on the DGS equivalent-circuit model, show excellent agreements with the electromagnetic (EM) simulation. Further, our method is applied effectively to design a low-pass filter (LPF) with DGS. Comparison between simulation and measurement confirm the validity of the LPF configuration and design procedure. Simple structure and high power handling capability are obtained from the proposed LPF.